Modelagem preditiva do comportamento de operações de pista da aviação comercial nos aeroportos internacionais do Galeão, Brasília, Guarulhos e Recife - Silva, Adriano Duarte da (2016)
The Brazilian aviation went through moments of supply and demand growth in the last decade, which triggered investment and plan decisions aiming at improving the Brazilian airspace control system and airports infrastructure as well as the services offered by airline companies (for instance aviation fuel demand increase). The main objective of this work is to contribute to the creation of a predictive model of takeoffs and landings for the short and medium run. We use the Box-Jenkins model (ARMA), combined with covariates, to predict the amount of takeoffs and landings of commercial aviation in four Brazilian airports: Galeão Airport (Rio de Janeiro), Brasília Airport (Distrito Federal), Guarulhos Airport (São Paulo) and Recife Airport (Pernambuco). We find that the models fit well in the short run, but in the medium run in forecast events such as the recent Brazilian economic crises can damage the predictions. The data analyzed in this work is owned by The Management Center of Air Navegation (CGNA), which is a military unit subordinated to the Departamento de Controle do Espaço Aéreo (DECEA). Therefore, the predictability of the demand for air traffic will help in the allocation of resources for air traffic management.